Determinants and Consequences of Financial Hardship Among Adult Survivors of Childhood Cancer: A Report From the St. Jude Lifetime Cohort Study. (1st August 2018) - Huang, I-Chan; Bhakta, Nickhill; Brinkman, Tara M; Klosky, James L; Krull, Kevin R; Srivastava, DeoKumar; Hudson, Melissa M; Robison, Leslie L
Abstract: Background: Financial hardship among survivors of pediatric cancer has been understudied. We investigated determinants and consequences of financial hardship among adult survivors of childhood cancer. Methods: Financial hardship, determinants, and consequences were examined in 2811 long-term survivors (mean age at evaluation = 31.8 years, years postdiagnosis = 23.6) through the baseline survey and clinical evaluation. Financial hardship was measured by material, psychological, and coping/behavioral domains. Outcomes included health and life insurance affordability, retirement planning, symptoms, and health-related quality of life (HRQOL). Odds ratios (ORs) estimated associations of determinants with financial hardship. Odds ratios and regression coefficients estimated associations of hardship with symptom prevalence and HRQOL, respectively. All statistical tests were two-sided. Results: Among participants, 22.4% (95% confidence interval [CI] = 20.8% to 24.0%), 51.1% (95% CI = 49.2% to 52.9%), and 33.0% (95% CI = 31.1% to 34.6%) reported material, psychological, and coping/behavioral hardship, respectively. Risk factors across hardship domains included annual household income of $39 999 or less vs $80 000 or more (material OR = 3.04, 95% CI = 2.08 to 4.46, psychological OR = 3.64, 95% CI = 2.76 to 4.80, and coping/behavioral OR = 4.95, 95% CI = 3.57 to 6.86) and below high school attainment vs college graduate or above (material OR = 2.22, 95% CI = 1.45 to 3.42, psychological OR = 1.75, 95% CI = 1.18 to 2.62, and coping/behavioral OR = 2.05, 95% CI = 1.38 to 3.06). Myocardial infarction, peripheral neuropathy, subsequent neoplasm, seizure, stroke, reproductive disorders, amputation, and upper gastrointestinal disease were associated with higher material hardship (all P  < .05). Hardship across three domains was associated with somatization, anxiety and depression (all P  < .001), suicidal ideation (all P  < .05), and difficulty in retirement planning (all P  < .001). Survivors with hardship had statistically significantly lower HRQOL (all P  < .001), sensation abnormality (all P  < .001), and pulmonary (all P  < .05) and cardiac (all P  < .05) symptoms. Conclusions: A substantial proportion of adult survivors of childhood cancer experienced financial hardship. Vulnerable sociodemographic status and late effects were associated with hardship. Survivors with financial hardship had an increased risk of symptom prevalence and impaired HRQOL.